Implementation of smart shelf system prototype using Radio Frequency Identification Technology and Wireless Transceiver Modules - Jugo, Tyrone C. (2007)
Smart Shelf is a shelf that keeps track of all items placed on top of it. Smart Shelf can individually identify items stored in it, pinpointing the position of these items and documenting activities performed on these items. Currently implemented Smart Shelf systems used Radio Frequency Identification (RFID) technology. However, cable wires were used to interface various RFID readers with a central server which tends the system to be cumbersome and, thus, restricting the system from becoming mobile and portable. The group implemented a Smart Shelf system prototype using RFID technology. The system was characterized in terms of antenna position inside the bin, transmit power, read range, and read rate. The Smart Shelf system was also integrated with COTS2 transceiver modules. The transceiver modules would be responsible for wirelessly configuring the RFID reader and transferring data gathered by the reader to a remote base station and thus eliminating the cumbersome and expensive use of coaxial cables in monitoring the readers. The system achieved a longer read range and a higher read rate when the transmit power level of the reader is configured to 25dBm up to its maximum, 27dBm. The read range achieved by the system at this range of power level was 50cm which is almost the size of the bin width. The highest read rate percentage using only one antenna was 90%. However, is the system used three antennas placed at different positions inside a bin, 100% read rate was achieved.